Radikale Zystektomie: pro laparoskopisch = Radical cystectomy : pro laparoscopic - Rassweiler, Jens; Godin, Konstantin; Gözen, Ali Serdar (Der Urologe, 2012)
Although the technical feasibility of laparoscopic radical cystectomy (LRC) has been proven and the procedure has been accepted in the EAU guidelines 2011 as a valid alternative, its actual position has to be determined. On the one hand the advantages of LRC (less blood loss, lower transfusion rates, shorter analgesia time) have been proven in retrospective studies; however, the technical difficulties of purely laparoscopic urinary diversion result in very long operating times and in cases of a laparoscopic-assisted creation of a neobladder, the question of the advantage of this approach remains doubtful. Despite case reports of port metastases and peritoneal carcinosis following laparoscopic and robot-assisted radical cystectomy, there is no difference in terms of oncological long-term data (up to 10 years) between laparoscopy and open surgery performed at centres of excellence. Evidently, the curative options for the patients do not depend on the type of surgery (open versus minimally invasive) but on the efficacy of adjuvant treatment strategies (polychemotherapy). Currently it is believed that LRC should be considered for patients with low risk of progression (pT1-2). The final position of laparoscopic radical cystectomy can only be evaluated in a multicentric randomized controlled trial.